Emerging Markets Are Catching Up: Economic or Financial Integration? - Akbari, Amir; Ng, Lilian; Solnik, Bruno (Journal of Financial and Quantitative Analysis, 2020)
We propose a simple metric to measure two aspects of market integration, namely, economic integration (defined as a common cash-flow dynamic) and financial integration (defined as a common risk-pricing dynamic) and then examine their evolution through time while controlling for volatility. We find that developed (DEV) countries exhibit greater degrees of financial and economic integration than emerging (EMG) markets. Although the financial integration gap between these markets remains large throughout the sample period, the EMG economies are catching up with their DEV counterparts in recent years; their level of economic integration has reached that of DEV countries.